The Influence of Parental Attention, Social Media, and Religiosity on Adolescent Moral Development: A Literature Review - Adib, Abdul (Al-Tadzkiyyah: Jurnal Pendidikan Islam, 2025)
This article systematically reviews the influence of parental attention, social media, and religiosity on adolescent moral development. The digital era has reshaped adolescents’ patterns of interaction, significantly influencing their values, morality, and behavioral orientations. Drawing upon 45 empirical and conceptual studies published between 2015 and 2025 across psychology, education, sociology, and communication disciplines, the review synthesizes findings on the interplay of these three determinants. Results confirm that parental involvement is a critical predictor of moral stability, social media exerts ambivalent effects depending on content quality and parental mediation, and religiosity consistently functions as a protective factor strengthening moral resilience. The novelty of this study lies in its integrative perspective, combining three strands of literature often treated separately, and thus offering a more comprehensive ecological understanding of adolescent moral development in family, digital, and religious contexts. The review further emphasizes the need for collaborative approaches involving families, educational institutions, and religious communities to promote adolescent moral resilience in the digital age.